Autoantigen-specific immunosuppression with tolerogenic peripheral blood cells prevents relapses in a mouse model of relapsing-remitting multiple sclerosis. Issue 1 (December 2016) - Kleist, Christian; Mohr, Elisabeth; Gaikwad, Sadanand; Dittmar, Laura; Kuerten, Stefanie; Platten, Michael; Mier, Walter; Schmitt, Michael; Opelz, Gerhard; Terness, Peter
Abstract Background Dendritic cells (DCs) rendered suppressive by treatment with mitomycin C and loaded with the autoantigen myelin basic protein demonstrated earlier their ability to prevent experimental autoimmune encephalomyelitis (EAE), the animal model for multiple sclerosis (MS). This provides an approach for prophylactic vaccination against autoimmune diseases. For clinical application such DCs are difficult to generate and autoantigens hold the risk of exacerbating the disease. Methods We replaced DCs by peripheral mononuclear cells and myelin autoantigens by glatiramer acetate (Copaxone® ), a drug approved for the treatment of MS. Spleen cells were loaded with Copaxone®, incubated with mitomycin C (MICCop ) and injected into mice after the first bout of relapsing-remitting EAE. Immunosuppression mediated by MICCop was investigated in vivo by daily assessment of clinical signs of paralysis and in in vitro restimulation assays of peripheral immune cells. Cytokine profiling was performed by enzyme-linked immunosorbent assay (ELISA). Migration of MICCop cells after injection was examined by biodistribution analysis of111 Indium-labelled MICCop . The number and inhibitory activity of CD4+ CD25+ FoxP3+ regulatory T cells were analysed by histology, flow cytometry and in vitro mixed lymphocyte cultures. In order to assess the specificity of MICCop -induced suppression, treated EAE mice were challenged with the control protein ovalbumin. Humoral and cellular immune responses were then determined by ELISA and in vitro antigen restimulation assay. Results MICCop cells were able to inhibit the harmful autoreactive T-cell response and prevented mice from further relapses without affecting general immune responses. Administered MICCop migrated to various organs leading to an increased infiltration of the spleen and the central nervous system with CD4+ CD25+ FoxP3+ cells displaying a suppressive cytokine profile and inhibiting T-cell responses. Conclusion We describe a clinically applicable cell therapeutic approach for controlling relapses in autoimmune encephalomyelitis by specifically silencing the deleterious autoimmune response.